2017
DOI: 10.1038/s41598-017-17674-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods to measure central and peripheral oxytocin concentrations in human and non-human primates

Abstract: Oxytocin (OT) concentration in the blood is considered to be a marker of its action in the brain. However, two problems have emerged when measuring OT level in the blood. First, it is unclear whether different methods of assessment lead to similar OT values. Second, it is unclear if plasma OT concentrations is informative on what OT does in the brain. To clarify these issues, we collected cerebrospinal fluid (CSF) from the brain ventricle of 25 patients during surgery to compare with plasma OT after simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 53 publications
8
59
1
1
Order By: Relevance
“…Axonal release of OT in the brain and in the circulatory system seem to be coordinated as central OT and peripheral OT in animals can be released simultaneously ( Wotjak et al, 1998 ). In humans, a correlation was shown between plasma and brain OT indicating that peripheral OT represents a suitable proxy of central OT ( Lefevre et al, 2017 ). It is also important to consider that, as they share a common ontogenetic origin from ectoderm, both brain and skin tissues contain similar collagenous proteins, reticulin, vasculature, and connective tissues such as fibroblasts and adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axonal release of OT in the brain and in the circulatory system seem to be coordinated as central OT and peripheral OT in animals can be released simultaneously ( Wotjak et al, 1998 ). In humans, a correlation was shown between plasma and brain OT indicating that peripheral OT represents a suitable proxy of central OT ( Lefevre et al, 2017 ). It is also important to consider that, as they share a common ontogenetic origin from ectoderm, both brain and skin tissues contain similar collagenous proteins, reticulin, vasculature, and connective tissues such as fibroblasts and adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral levels of OT (OTp) are assumed to reflect central releases of OT (OTc) in rats ( Wotjak et al, 1998 ) and humans ( Lefevre et al, 2017 ) with some procedural exceptions. Blood samples (0.5–0.7 mL) were taken 1–2 d prior to behavioural assessments ( Faraji et al, 2014 ) to measure plasma concentration of OT using solid phase radioimmunoassay (RIA) ( Alburges et al, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, direct manipulation of the OT system by focal infusion into the macaque brain alters social gaze, prosocial decisions (Chang et al, 2015) and behavioral synchrony (Jiang & Platt, 2018), and the release of serotonin in brain regions implicated in social processing (Lefevre, Richard, et al, 2017). OT receptors in the rhesus monkey brain are highly expressed in regions involved with visual processing, including the nucleus basalis of Meynert, the pedunculopontine tegmental nucleus, the superficial gray layer of the superior colliculus, the trapezoid body, and the ventromedial hypothalamus (Freeman, Inoue, Smith, Goodman, & Young, 2014).…”
Section: Preclinical Model Systemsmentioning
confidence: 99%
“…A small number of nonhuman primate studies have evaluated pharmacokinetic outcomes associated with these different routes of administration, though methodological differences have contributed to inconsistent findings. While rodent studies have demonstrated increases in both brain and plasma OT levels 30–60 min following nasal administration (Neumann, Maloumby, Beiderbeck, Lukas, & Landgraf, 2013), the relationship between central and peripheral levels of OT remains unclear, possibly due to temporal differences in OT bioavailability (Lefevre, Mottolese, et al, 2017). Here, we briefly summarize nonhuman primate studies reporting cerebrospinal fluid (CSF) outcome measures, which provide a direct and relatively noninvasive assessment of central nervous system (CNS) penetration routinely available for nonhuman primates.…”
Section: Ot Administration Routes and Pharmacokineticsmentioning
confidence: 99%
“…Simplifiant encore l'équation, une étude récente tend à montrer l'extrême variabilité existant entre différentes méthodes de dosage de l'ocytocine, fragilisant l'intégralité des conclusions basées sur les dosages dans le LCR et plasmatiques [45]. La controverse quant au mode d'administration de l'ocytocine, et à sa mesure, reste donc à ce jour réelle.…”
Section: Controverses ?unclassified